Exploring the Cognitive Growth Stages in Perry Theory and their Application for Higher Level Mathematics Learning - Kunwar, Rajendra; Acharya, Nara Hari; GC, Laxmi (Tribhuvan University Journal, 2024)
This article explores the cognitive growth stages in Perry’s theory, its applications, and relevancies in higher-level mathematics learning using a review-based method. Perry’s theory of intellectual and ethical development provides a framework for understanding and applying effective principles in mathematics education. The article examines the developmental progressions outlined in Perry’s stages and their alignment with the cognitive shifts required for advanced mathematical understanding. The study focuses on the application of Perry’s theory in the context of higher-level mathematics education to gain insights into how to nurture students’ cognitive development and equip them with the skills for advanced mathematical competency. The article concludes by discussing the relevancies of Perry’s theory in different dimensions of mathematics learning shaping effective mathematics curriculum and pedagogy. The findings highlight the importance of considering Perry’s framework in designing instructional strategies that promote deeper understanding, cognitive flexibility, and critical thinking in higher-level mathematics learning.